2012
DOI: 10.1130/g33522.1
|View full text |Cite
|
Sign up to set email alerts
|

Onset of aseismic creep on major strike-slip faults

Abstract: International audienceTime series analysis of spaceborne synthetic aperture radar (SAR) data, GPS measurements, and fi eld observations reveal that the central section of the Izmit (Turkey) fault that slipped with a supershear rupture velocity in the A.D. 1999, Mw7.4, Izmit earthquake began creeping aseismically following the earthquake. Rapid initial postseismic afterslip decayed logarithmically with time and appears to have reached a steady rate comparable to the preearthquake full fault-crossing rate, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
82
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 24 publications
14
82
1
Order By: Relevance
“…by Karabacak et al (2011) [9] to calculate the rate of 6.8-10.0±4.0 mm/yr and 9.1-10.1±4.0 mm/yr. Cakir et al, (2012) [2] and Cetin et al, (2014) [3] reported that the rate is not stable along the fault and reaches a maximum of 20±2 mm/ yr 20km to the east from Ismetpasa (Figure 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…by Karabacak et al (2011) [9] to calculate the rate of 6.8-10.0±4.0 mm/yr and 9.1-10.1±4.0 mm/yr. Cakir et al, (2012) [2] and Cetin et al, (2014) [3] reported that the rate is not stable along the fault and reaches a maximum of 20±2 mm/ yr 20km to the east from Ismetpasa (Figure 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…The important point of the creep is the threshold of the aseismic slip rate. If the creep motion has velocity equal or longer than long-term slip rate along the fault, the fault will continue to slip freely and will not produce destructive earthquake (Cakir et al, 2012). Conversely, if the aseismic slip rate is lower than the long-term slip rate of the fault, it is possible that the fault can produce the destructive earthquake (Karabacak et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The LIDAR technology was also used by Karabacak et al (2011) to calculate the rate of 6.8-10.0±4.0 mm/yr and 9.1-10.1±4.0 mm/yr. Cakir et al (2012) and Cetin et al (2014) reported that the rate is not stable along the fault and reaches a maximum of 20±2 mm/yr 20km to the east from Ismetpasa (Figure 3 and 4). Another aseismic creep segment on the NAF was reported by Karabacak et al (2011) in Destek village on the northeast of the Corum.…”
Section: Tectonic Settingsmentioning
confidence: 99%
See 2 more Smart Citations